MRI brain findings of cerebral malaria in children with acute encephalitis syndrome: a prospective study in 60 patients - Yadav, Vibha; Thora, Sharad; Choudhary, Prachi (International Journal of Research in Medical Sciences, 2020)
Background: Acute encephalitis syndrome (AES) is defined as a person of any age group, at any time of the year with the acute onset of fever and change in mental sensorium (including confusion, disorientation, coma or inability to talk) and/or new onset of convulsions (excluding febrile seizures). Encephalitis is a inflammation of brain tissue which presents as a diffuse and/or a focal neuropsychological dysfunction and inflammation of adjacent meningitis. Objectives were to determine clinicoepidemiological profile in AES with special to reference cerebral malaria and to study various MRI findings in patients of AES especially in cerebral malaria. Methods: A prospective study of all cases of fever with unconsciousness or altered sensorium with or without convulsions admitted in PICU of MYH and CNBC Indore. Inclusion criteria was all those children who were previously neurologically normal, of age 1-14 years, patients with fever (<15days) with altered sensorium, with or without seizures and who stay in hospital long enough to complete essential diagnostic work up which includes (CBC with peripheral smear, RFT, LFT, MP, S. electrolytes, CSF, MRI brain). Results: The final study group comprised of 60 patients with age group 1-14 yrs and male to female ratio was 1.07:1. Patients with diagnosis of cerebral malaria were 17. High grade fever, headache, altered sensorium, generalized seizures In general examination pallor was present in 52.9%, icterus in 35.29% cases of cerebral malaria. Splenomegaly (70.5%) was more common finding than hepatomegaly (58.8%) in cerebral malaria. GCS was>6 in most cases, fundus abnormality and meningeal irritation was absent in all cases of cerebral malaria. MRI of brain in cerebral malaria was mostly normal, in (47.05%), second most common we get hyperintensity in periventricular and corpus callosum areas (23.52%), hyperintensity in basal ganglia and thalamus was found in17.64% cases and white matter changes in 2 cases. The final outcome of all cerebral cases was good, all were discharged, and there was no mortality. Conclusions: Our result demonstrate that cerebral malaria is a common cause of acute febrile encephalopathy in children. Presence of plasmodium falciparum is essential for diagnosis of cerebral malaria. No specific lesions have been identified in MRI brain.